The Role of VLBI in Astrophysics, Astrometry and Geodesy - Mantovani, Franco; Kus, Andrzej (NATO Science Series II: Mathematics, Physics and Chemistry, Mathematics, Physics and Chemistry, 2005)
A masterly survey of the last 13 years of Very Long Baseline Interferometry, reviewed in light of the most advanced astronomical observations. Topics covered include: Nonthermal emission from extragalactic radio sources; Principles of synchrotron emission in relation to astrophysics; Theory of relativistic jets; Young, powerful radio sources and their evolution; Scintillation in extragalactic radio sources; Radio and optical interferometry; Radio polarimetry; Unified schemes; Deep fields; Tropospheric and ionospheric phase calibration; Supernovae; VLBI for geodesy and geodynamics.